The Efficacy of Intravenous Insulin Infusion in the Management of Hypertriglyceridemia-Induced Pancreatitis in a Rural Community Hospital - Khalid Sawalha MD; Anthony Kunnumpurath MBBS; Gilbert-Roy Kamoga MD, FACP (SAGE Publishing, 2020)
A 28-year-old female presented to the emergency room with epigastric pain, nausea, and vomiting; her lipase was elevated, and computed tomography of abdomen showed evidence of acute pancreatitis. Her past medical history was significant for poorly controlled insulin requiring type 2 diabetes mellitus and 2 previous admissions for hypertriglyceridemia-induced pancreatitis. Due to the severity of her pancreatitis presentation, she was admitted to the intensive care unit. She received aggressive intravenous fluid hydration and was started on an insulin drip. Apheresis was strongly considered given the degree of her hypertriglyceridemia (11 602 mg/dL), but there was no timely access to this treatment option. She, however, significantly improved with insulin therapy alone. Her triglyceride levels decreased rather quickly to 4783 mg/dL within 24 hours and by the fourth day of admission were comfortably <1000 mg/dL with insulin infusion along with clinical improvement. She was discharged on niacin and insulin therapy along with her home medications of statin and fenofibrate.